2019
DOI: 10.1242/jcs.231431
|View full text |Cite
|
Sign up to set email alerts
|

Parcas is the predominant Rab11-GEF for rhodopsin transport in Drosophila photoreceptors

Abstract: Rab11 is essential for polarized post-Golgi vesicle trafficking to photosensitive membrane rhabdomeres in Drosophila photoreceptors. Here, we found that Parcas (Pcs), recently shown to have guanine nucleotide exchange (GEF) activity toward Rab11, co-localizes with Rab11 on the trans-side of Golgi units and post-Golgi vesicles at the base of the rhabdomeres in pupal photoreceptors. Pcs fused with the electron micrography tag APEX2 localizes on 150-300 nm vesicles at the trans-side of Golgi units, which are pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 44 publications
(57 reference statements)
0
19
0
Order By: Relevance
“…REs localized to the trans-side of Golgi stacks in Drosophila S2 cells By using electron microscopy, we also investigated the localization of RE markers in Schneider 2 (S2) cells derived from Drosophila embryos (Schneider, 1972). We have recently reported that Parcas (Pcs) is the predominant Rab11-GEF in fly photoreceptors and intensively colocalizes with Rab11 (Otsuka et al, 2019). In S2 cells, V5::Pcs localized to the trans-side of Golgi stacks (Fig.…”
Section: Re Markers Partially Colocalize With Tgn Markers In Drosophimentioning
confidence: 96%
See 4 more Smart Citations
“…REs localized to the trans-side of Golgi stacks in Drosophila S2 cells By using electron microscopy, we also investigated the localization of RE markers in Schneider 2 (S2) cells derived from Drosophila embryos (Schneider, 1972). We have recently reported that Parcas (Pcs) is the predominant Rab11-GEF in fly photoreceptors and intensively colocalizes with Rab11 (Otsuka et al, 2019). In S2 cells, V5::Pcs localized to the trans-side of Golgi stacks (Fig.…”
Section: Re Markers Partially Colocalize With Tgn Markers In Drosophimentioning
confidence: 96%
“…3B-D). By using the genetic EM-tag ascorbate peroxidase 2 (APEX2; Martell et al, 2017), we also found Pcs localization to the cytoplasmic surface of 150-300 nm distorted vesicles or cisternae, which often associate with Golgi stacks (Otsuka et al, 2019). To clarify Pcs localization in regard to cistrans polarity of Golgi stacks, we performed double-APEX-labeling of GalT and Pcs.…”
Section: Re Markers Partially Colocalize With Tgn Markers In Drosophimentioning
confidence: 99%
See 3 more Smart Citations